THE ESTIMATION OF DISPERSION BEHAVIOR IN DISCRETE FRACTURED NETWORKS OF ANDESITE IN LAN-YU ISLAND, TAIWAN - Cheng-Haw L.; Chen-Chang L.; Bih-Shan L. (My University, 2007)
This study was based on the discrete fracture model to investigate the influence of fracture parameters on the solute transport in the fractured rocks of andesite in Lan-Yu island, Taiwan. In the simulation cases, the centers of fractures, fracture lengths and apertures were assumed to have Poisson’s distribution, negative exponential distribution and lognormal distribution, respectively. With the above assumptions, constructing the discrete fracture model became practicable. Using the mass-balance equation with specified boundary conditions, the flow field in the rock was solved. Then particles were released under the flow field. Monte Carlo method was used assuming that the amount of particles was proportional to the flow rates to get the particle accumulated percentage breakthrough curve and to estimate the dispersion coefficient. On the basis of the discrete fracture model, it was possible to evaluate the property of dispersion behavior of andesite in Lan-Yu Island with flow and transport mechanism. Properties of the dispersion behavior such as the relation between distance and traveling-time (ln〈r 2〉 and ln 〈t〉), anisotropic behavior, and the overall dispersion coefficient in a fracture network were characterized: the slope value of ln〈r 2〉 and ln〈t〉 was 1.64 an indication of non-Fickian dispersion, the particles dispersion along the flow (D11) was bigger than that perpendicular to the flow (D22), and the dispersion coefficient by this study was 0.91 m comparing the value 1 m from Sauty’s method.
Keywords: FRACTURE NETWORKS; PARTICLE TRACKING; MOTE CARLO SIMULATION; DISPERSION BEHAVIOR; ANDESITE